Physiology, Pharmacology and Pathology of the Blood-Brain Barrier - Cader, Zameel; Neuhaus, Winfried (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents a comprehensive collection of current knowledge and leading research about the blood-brain barrier. The chapters are organized in four main parts providing basic information and novel insights about the physiology of the blood-brain barrier, the challenges related to finding and developing drugs crossing the blood-brain barrier, experimental methods to study the blood-brain barrier and the role of the blood-brain barrier in disease mechanisms and its consequences for drug development. In the first part the readers will discover the structure, function and developmental aspects of the blood-brain barrier and gain novel insights into the complexity and functionality of the neurovascular unit and energy metabolism of brain endothelial cells. Chapters of the second part focus on translational challenges from the bench to the bedside in CNS drug development, shed light on the importance to understand the brain distribution of drugs related to their efficacy, elaborate on general pharmacokinetic considerations for CNS drugs and introduce current and novel drug delivery strategies to overcome the blood-brain barrier. The experimental part of the book covers mathematical and in vitro models as well as animal and human methods in blood-brain barrier research. Specific emphasis is set on the description of the methods, the role of species differences for data interpretation, novel human models based on stem cells with the potential for personalized medicine and technical considerations and tips helpful for readers interested in working with these models. In the fourth part particular attentions is given to the blood-brain barrier, its changes and participation during disease progression. Chapters summarize alterations of the blood-brain barrier that are present in common disorders such as Alzheimer's disease, multiple sclerosis, stroke, traumatic brain injury, epilepsy and brain tumors. Present therapies will be discussed and the consequences for novel treatment approaches that need to bypass the blood-brain-barrier will be explored. In addition, experts discuss the question in how far changes at the blood-brain barrier are causally linked to disease progressions and consequently could serve as therapeutic targets. This collection is designed to appeal to a wide readership from students through basic and applied scientist to pharmacologists, medical doctors and stakeholders from the pharmaceutical industry and regulatory affairs. Due its comprehensive content the book has the potential to become a standard work in the field of blood-brain barrier research.
From the contents: Preface -- Part I: Background on the Blood Brain Barrier - structure/function.-Part II: Challenges with finding drugs to cross the BBB/not cross BBB -- Part III: Experimental Methods to study BBB - in vitro and in vivo -- Part IV: BBB and Diseases: Novel treatment approaches from a BBB perspective. .
Keywords: Pharmacology; Human physiology; Medical microbiology; Pathology; Neurosciences; Pharmacology; Human Physiology; Medical Microbiology; Pathology; Neuroscience